Narrativas Sobre Comunicación, Jerarquía Y Límites En Docentes Activas Con Indicadores De Estrés. (2019)
The objective of the following investigation is to describe the communication, hierarchy and family limits of 5 professors, which are currently working and showing signs of stress. The theorical fundations proposed for this investigation were based on a systematic approach. The methodology used on the following investigation is quantitative. The data collection method was based on a semi-structured interview developed by the document's authors, based on the mentioned document an, interpretation of each one of the participant's narrative, for a better understanding 3 different formats are used. The first format contains the professors' interviews, highlighted in 3 different colors to point out the categories to inquire. The second format is based on the codification of the important elements of the interviews and the third format is the interpretation of the theorical contrast and discussion between the 5 participants